Calix[4]pyrrole‐Grafted Gold Nanoparticles as a Turn‐On Fluorescence Sensor for Noxious Fungicide Dimoxystrobin and Their Anti‐Cancer Activity against the KB‐3‐1 Cell Line. Issue 11 (14th March 2023) - Pomal, Nandan C.; Bhatt, Keyur D.; Kundariya, Dinesh S.; Desai, Riya A.; Bhatt, Vaibhav; Kongor, Anita
Abstract: A rapid and easy approach for producing very stable gold nanoparticles has been discovered. Calix[4]pyrrole tetrahydrazide (CPTAH) was utilized effectively in the synthesis of gold nanoparticles as a reducing and stabilizing agent. These functionalized AuNPs were characterized by Surface Plasmon Resonance, Transmission Electron Microscopy, Selected Area Electron Diffraction, and Energy Dispersive X‐ray techniques. CPTAH‐AuNPs possessed a particle size of 11±2 nm and are highly stable at pH 7.0 for more than 150 days. The selectivity and sensitivity of CPTAH‐AuNPs as a fungicide sensor was assessed for Metalaxyl, Mancozeb, Tebuconazole, Tricyclozole, Dimoxystrobin, Kresoxim‐methyl, and Carbendazim, amongst which Dimoxystrobin (DMX) was sensed exclusively with naked eyes by means of aggregation of CPTAH‐AuNPs with a detection limit of the order of 5 ppm using "Turn‐on" fluorescence enhancement. Additionally, the CPTAH‐AuNPs were found to be effective cytotoxic agent against the human cervix cancer cell line KB‐3‐1 with IC50 value of 64.63 μg/mL which admits the employability of CPTAH‐AuNPs in the study of development of anti‐cancer drug. Abstract : The reducing and stabilizing agent calix[4]pyrrole tetrahydrazide was utilized in a one‐pot synthesis procedure that yielded stable CPTAH‐AuNPs which are the manifold entities, with size of 11±2 nm and spherical, that have been stable for more than 150 days. CPTAH‐AuNPs are "Turn‐on" fluorescent sensor selectively and sensitively for toxic fungicide Dimoxystrobin. CPTAH‐AuNPs also inhibited the growth of the human cervix cancer cell line KB‐3‐1.